Model Kepemimpinan Kolaboratif dalam Sekolah Berbasis Nilai Islam - Zikroatul Nurul Uula; Muhammad Ali (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The leadership style of school principals in the context of modern Islamic education has not been widely explored in depth, especially related to the dynamics of relationships and real experiences that combine Islamic values with effective leadership practices in Muhammadiyah-based secondary schools. This study aims to analyze the principal's leadership style at SMP Muhammadiyah 2 Boyolali Special Program with the hypothesis that democratic and participative leadership styles are able to improve teacher motivation and performance through the creation of a supportive, communicative, and trusting work environment. The research used a qualitative approach with a phenomenological descriptive design, involving the Principal as the main subject as well as the Vice Principal and teachers as supporting informants, with data collection through observation, in-depth interviews, and documentation analyzed using the Miles and Huberman model. The results show that principals apply democratic and participatory leadership styles that are open to teacher input, use a performance and loyalty-based assignment system, conduct regular coordination and evaluation, make decisions collectively through deliberation, provide motivational stimulation through training and rewards, and implement a structured and collaborative problem handling system. The findings confirm that a combination of democratic, participatory, transformational and instructional leadership styles proved effective in creating a collaborative work climate, supporting teachers' professional development and ensuring responsive decision-making to the needs of Islamic values-based schools.